A role for migration‐linked genes and genomic islands in divergence of a songbird. Issue 19 (8th July 2014) - Ruegg, Kristen; Anderson, Eric C.; Boone, Jason; Pouls, Jazz; Smith, Thomas B.
Abstract Next‐generation sequencing has made it possible to begin asking questions about the process of divergence at the level of the genome. For example, recently, there has been a debate around the role of 'genomic islands of divergence' (i.e. blocks of outlier loci) in facilitating the process of speciation‐with‐gene‐flow. The Swainson's thrush, Catharus ustulatus, is a migratory songbird with two genetically distinct subspecies that differ in a number of traits known to be involved in reproductive isolation in birds (plumage coloration, song and migratory behaviour), despite contemporary gene flow along a secondary contact zone. Here, we use RAD‐PE sequencing to test emerging hypotheses about the process of divergence at the level of the genome and identify genes and gene regions involved in differentiation in this migratory songbird. Our analyses revealed distinct genomic islands on 15 of the 23 chromosomes and an accelerated rate of divergence on the Z chromosome, one of the avian sex chromosomes. Further, an analysis of loci linked to traits known to be involved in reproductive isolation in songbirds showed that genes linked to migration are significantly more differentiated than expected by chance, but that these genes lie primarily outside the genomic islands. Overall, our analysis supports the idea that genes linked to migration play an important role in divergence in migratory songbirds, but we find no compelling evidence that the observed genomic islands are facilitating adaptive divergence in migratory behaviour.